Accommodation Strategies IN Cross-cultural Communication of Rohingya Ethnicity in Interacting with The Community of Pekanbaru City - Ringgo Eldapi Yozani; Qori Gita Cahyani; Nova Yohana; Mutia Novela Sari; Tutut Ismi Wahidar; Riyanda Elsera Yozani (Nyimak: Journal of Communication, 2026)
Pekanbaru City has become one of the destinations for asylum seekers, including members of the Rohingya ethnic group who have experienced forced migration from Myanmar. This study aims to examine the strategies of convergence, divergence, and the phenomenon of over-accommodation in communication interactions between Rohingya refugees and the local community. The research employs a qualitative method using a symbolic interaction approach. The findings reveal that the communication accommodation practices of the Rohingya refugees are dynamic, reflecting both efforts to adapt to the host community and attempts to maintain their cultural identity. Convergence strategies are demonstrated through the use of the Indonesian language, open nonverbal communication, and cultural adjustments such as shared religious practices with the local population. In contrast, divergence strategies are reflected in the continued use of the Rohingya language among fellow refugees, the tendency to withdraw from conversations they do not fully understand, and the preservation of traditional dietary habits, clothing styles, and social roles. Furthermore, the phenomenon of over-accommodation appears in the form of reliance on refugees who are more proficient in Indonesian to act as communication intermediaries, which may limit opportunities for independent adaptation. These findings highlight that the communication accommodation process among Rohingya refugees in Pekanbaru is complex and shaped by the simultaneous need for social integration and cultural preservation.Keywords: Communication accommodation, Rohingya, refugeesÂ ABSTRAKPekanbaru merupakan salah satu wilayah tujuan bagi imigran pencari suaka, termasuk Etnis Rohingya yang mengalami migrasi paksa dari Myanmar. Penelitian ini bertujuan untuk menganalisis strategi konvergensi, divergensi, serta fenomena akomodasi berlebihan dalam interaksi komunikasi antara pengungsi Rohingya dan masyarakat lokal. Penelitian ini menggunakan metode kualitatif dengan pendekatan interaksi simbolik. Hasil penelitian menunjukkan bahwa akomodasi komunikasi Etnis Rohingya bersifat dinamis, yang mencerminkan upaya adaptasi sekaligus pelestarian identitas budaya mereka. Strategi konvergensi terlihat melalui penggunaan Bahasa Indonesia, komunikasi nonverbal yang terbuka, serta penyesuaian budaya seperti praktik keagamaan yang serupa dengan masyarakat setempat. Sementara itu, strategi divergensi tampak pada penggunaan Bahasa Rohingya di antara sesama pengungsi, kecenderungan menarik diri dari percakapan yang tidak dipahami, serta pelestarian kebiasaan makan, gaya berpakaian, dan peran sosial tradisional. Selain itu, fenomena akomodasi berlebihan muncul dalam bentuk ketergantungan pada pengungsi yang lebih fasih berbahasa Indonesia sebagai perantara komunikasi, yang berpotensi menghambat proses adaptasi mandiri. Temuan ini menunjukkan bahwa proses akomodasi komunikasi pengungsi Rohingya di Pekanbaru berlangsung secara kompleks dan dipengaruhi oleh kebutuhan adaptasi sekaligus upaya mempertahankan identitas budaya.Kata Kunci: Akomodasi komunikasi, Rohingya, pengungsi